Reinforcing the vast difference between the outcomes of spontaneous versus induced miscarriages - Maru, Laxmi; Verma, Monica; Khan, Tazeen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Information on incidence of spontaneous and induced abortion is crucial for identifying policy and programmatic needs aimed at reducing unintended pregnancies. In this study, we analyzed in detail the presentation, complications of abortions and procedure associated complications of spontaneous and induced miscarriages. Methods: The study was prospectively conducted on 200 patients from IPD of MGM Medical College, Indore over a period of two years and under the guidance of population council of India. The patients were divided into 2 groups of 100 patients each under spontaneous and induced miscarriages. Results: After matching the parity, age of mothers, gestational age at presentation and socioeconomic status the results were analyzed. 45% women presented with incomplete abortion followed by inevitable (20), missed (12) and complete abortion (19) in the spontaneous abortion group. In induced abortion group majority of women presented with failure of contraception, natural method use being the most common method of contraception. Young women preferred medical abortion while multiparous women went for surgical evacuation. Minor and tolerable side effects like mild bleeding pain nausea etc. were seen in medically supervised group of induced miscarriage. Major and life threatening complications were seen in the spontaneous abortion group like heavy bleeding, hypovolumic shock, septic abortion, foul smelling vaginal discharge, bowel injury and also one mortality was seen in the spontaneous abortion group. Conclusions: While appreciable progress has been made in legalizing and improving MTP services, the unmet needs continue to grow. Efforts should be made to make safe abortion facilities available to majority of population. At the same time awareness should be spread so that seeking abortion does not become an alternative to contraception.